Breaking the Chains: Unraveling the Intricate Interplay Between Labor Export and Food Import Dynamics in Nepal (Scholars' Journal, 2023)
Labor exports and food imports are two current Nepalese phenomena that are pertinent and have academic value in discussions. Although Nepal is well known for being an agricultural nation, recent years have seen a rise in labor shortages, underutilization of agricultural land, and food shortages. In this consideration, the aim of this paper is to examine the scenario of labor migration in relation to the food import dynamics in Nepal. Secondary data served as the basis for the examination. To explain the quantitative and qualitative data, a mixed method has been employed for the study. There is a direct correlation between the increasing proportion of labor exported from Nepal and the parallel decline in agricultural production and growing Nepal’s food import. The state’s economy always suffers when agricultural products are imported from other nations. In Nepal, the establishment of an independent economy is imperative. In order to create employment opportunities and optimize resource utilization, labor management is essential. Cereal and food imports indicate a potential economic crisis by indicating the outflow of national currency. Proper land use, commercialization, market access, technology transfer, and agricultural policies could all contribute to the country’s sustainable economic growth. It is urgent to break through the vicious circle of importing foods and exporting labour to revive the national economy of Nepal.